Beyond the Sinister and the Fantastic: Concept of the Telluric and Its Aplication in an Analysis of "Hamlet" - Espinosa, Antonio César Morón (Tropelías: Review of Literary Theory and Comparative Literature, 2019)
This article hopes to establish a new concept in literary theory in order to be used as a tool for the analysis of texts: telluric. Its specific research is carried out in two steps: first it has been framed within a theoretical universe with which keeps certain relationship. In a second movement, it confronts and emphasizes its contrasts with the fundamental concepts of that theoretical universe: the Freudian uncanny, «unheimlich», and the fantastic, «fantastique», from Todorov. Finally, in order to check its hermeneutic possibilities, the concept of telluric has been applied to the analysis of Hamlet.
Keywords: telluric; sinister; fantastic; Freud; Todorov; Hamlet